Was King Richard III Really Such a Bad Guy? - Peter Fear, Alan (Revista PHILIA | Filosofia, Literatura & Arte, 2024)
The historical figure of King Richard III of England has suffered defamation at the hands of Tudor propagandists and most pointedly from the quill of England’s most famous Bard. Consequently, popular memory has us believe that the king was indeed a sociopathic megalomaniac who murdered his own nephews in order to seize power. This paper examines and questions the historiography of Richard III, presents alternative options that absolve the King’s ill repute, and proposes that Richard III should be remembered as a heroic warrior King rather than a psychopathic tyrant of the Tudors’ and Shakespeare’s history.